2001
DOI: 10.1007/s003300101114
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the wrist and finger joints in inflammatory joint diseases at 1-year interval: MRI features to predict bone erosions

Abstract: The aim of this study was to assess the ability of MRI determined synovial volumes and bone marrow oedema to predict progressions in bone erosions after 1 year in patients with different types of inflammatory joint diseases. Eighty-four patients underwent MRI, laboratory and clinical examination at baseline and 1 year later. Magnetic resonance imaging of the wrist and finger joints was performed in 22 patients with rheumatoid arthritis less than 3 years (group 1) who fulfilled the American College of Rheumatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(71 citation statements)
references
References 31 publications
1
65
0
5
Order By: Relevance
“…In this context, MRI has become a valuable technique for early detection of bone erosions in RA (9). Reports of osteodestruction being detected by conventional radiography earlier and more frequently in the foot than in the hand joints (15)(16)(17) provide accumulating evidence that the foot may be primarily affected in the early stages of RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, MRI has become a valuable technique for early detection of bone erosions in RA (9). Reports of osteodestruction being detected by conventional radiography earlier and more frequently in the foot than in the hand joints (15)(16)(17) provide accumulating evidence that the foot may be primarily affected in the early stages of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Bone edema is known as a very early marker of inflammation and, in addition to synovitis, as a strong individual predictor of bone erosion in the MRI evaluation of hand RA, carrying a 6.5-fold risk of bone damage at the same site within 1 year (25,28). Longitudinal studies of patients with early RA showed that the total synovial volume in the finger joints and the presence of bone edema seem to be predictive of the number of bone erosions 1 year later and may be used in screening (9). As shown in our study, bone edema seems to be a typical MRI feature in patients with early RA, which usually 2100 OSTENDORF ET AL might not be found in patients with only nonspecific arthralgia (29).…”
Section: Discussionmentioning
confidence: 99%
“…In RA the early synovial proliferation preceded the erosions at the bone capsule interface [7,9,10•,30,31]. The erosion with adjacent BME were shown in RA to more likely progress than those without BME [31,32]. In PsA the entheseal bone marrow and soft tissue edema have been suggested to precede erosions, however, these suggestions need to be proved [4,12•].…”
Section: Image Analysismentioning
confidence: 96%
“…Various studies have reported that MRI pathology (synovitis, bone erosions or, most often, BME) of the wrist and MCP joints at disease onset in early RA predicts radiographic erosions [108,[126][127][128][129][130][131][132][133][134]. Some looked at the short-term predictive value of MRI after 1 year [108,126,128,130,131], whereas other studies had 2 [128,132], 3 [134], 5 [133], 6 [127], or 10 years [129] of follow-up.…”
Section: Prognosticationmentioning
confidence: 99%
“…Some looked at the short-term predictive value of MRI after 1 year [108,126,128,130,131], whereas other studies had 2 [128,132], 3 [134], 5 [133], 6 [127], or 10 years [129] of follow-up. All studies found MRI to be a highly significant predictor of radiographic erosions.…”
Section: Prognosticationmentioning
confidence: 99%